2014
DOI: 10.1371/journal.pone.0092228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prolonged Coldness on Survival and Fertility of Drosophila melanogaster

Abstract: The laboratory fruit fly, Drosophila melanogaster, is used widely in biological research, but the requirement to maintain stocks with a roughly biweekly generation time imposes substantial burdens of labor, potential cross-contamination and mutation accumulation. The purpose of this study was to assess the impact of prolonged cold stress or milder cooling on survivorship and fertility. The hypothesis was that cold storage would result in postponement of reproduction and a longer generation time. Flies of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Although this species originated in a tropical area, its status as a genetic model organism permitted important insights into the metabolic and genomic mechanisms involved in the interplay between cold tolerance and reproductive arrest (Kubrak et al, 2014). Although this has not been well tested, cold-adapted species are expected to maintain fertility after prolonged exposure to cold in order to succeed at high latitudes (Mockett and Matsumoto, 2014;Marshall and Sinclair, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although this species originated in a tropical area, its status as a genetic model organism permitted important insights into the metabolic and genomic mechanisms involved in the interplay between cold tolerance and reproductive arrest (Kubrak et al, 2014). Although this has not been well tested, cold-adapted species are expected to maintain fertility after prolonged exposure to cold in order to succeed at high latitudes (Mockett and Matsumoto, 2014;Marshall and Sinclair, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that diapause-terminated individuals are most likely to experience cold temperature of various durations during early spring (aseasonal short-term events that can not be predicted) which may influence their development, survival and reproduction, but receiving less attention (see Tauber et al 1986). Only a few studies follow the reproductive fitness of resultant females after insects have passed several live stages under the cold conditions (e.g., Jones & Kunz 1998;Chen et al 2008Chen et al , 2011Mockett & Matsumoto 2014). Our study investigated the effect of prolonged chilling duration of T. urticae eggs at 5 °C on egg hatching, immature development and survival as well as reproductive fitness of resultant females.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results clearly show that chilling for ≥ 48 hours significantly decreased the survival of deutonymphs which may be the cause of significantly lower total immature survival rate detected for chilling durations of ≥ 48 hours (Figure 1). Prolonged exposure to low temperatures associated with poor survival of immature stages is common (Hofsvang & Hågvar, 1977;Jones & Kunz 1998;Leopold 1998;Chen et al 2008;Colinet & Boivin 2011;Mockett & Matsumoto 2014). According to Storey & Storey (1988), Rojas & Leopold (1996) and Leopold (1998), it is suggested that despite the 'normal' development of eggs, oxidative stress caused by build-up of reactive oxygen species in eggs might have occurred during the lengthy exposure to lower temperature, and such oxidative stress was passed into and caused injury to the subsequent immature stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations